Citrullinome of Porphyromonas gingivalis Outer Membrane Vesicles: Confident Identification of Citrullinated Peptides - Larsen, Daniel Nyberg (Mol Cell Proteomics, 2020)
Porphyromonas gingivalis is a key pathogen in chronic periodontitis and has recently been mechanistically linked to the development of rheumatoid arthritis via the activity of peptidyl arginine deiminase generating citrullinated epitopes in the periodontium. In this project the outer membrane vesicles (OMV) from P. gingivalis W83 wild-type (WT), a W83 knock-out mutant of peptidyl arginine deiminase (ΔPPAD), and a mutant strain expressing PPAD with the active site cysteine mutated to alanine (C351A), have been analyzed using a two-dimensional HFBA-based separation system combined with LC-MS. For optimal and positive identification and validation of citrullinated peptides and proteins, high resolution mass spectrometers and strict MS search criteria were utilized. This may have compromised the total number of identified citrullinations but increased the confidence of the validation. A new two-dimensional separation system proved to increase the strength of validation, and along with the use of an in-house build program, Citrullia, we establish a fast and easy semi-automatic (manual) validation of citrullinated peptides. For the WT OMV we identified 78 citrullinated proteins having a total of 161 citrullination sites. Notably, in keeping with the mechanism of OMV formation, the majority (51 out of 78) of citrullinated proteins were predicted to be exported via the inner membrane and to reside in the periplasm or being translocated to the bacterial surface. Citrullinated surface proteins may contribute to the pathogenesis of rheumatoid arthritis. For the C351A-OMV a single citrullination site was found and no citrullinations were identified for the ΔPPAD-OMV, thus validating the unbiased character of our method of citrullinated peptide identification.